If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1(-3) = x Multiply -1 * -3 1 + 3 = x Combine like terms: 1 + 3 = 4 4 = x Solving 4 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -1x = x + -1x Combine like terms: x + -1x = 0 4 + -1x = 0 Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 2(3x+5)=26-(6-3x) | | 2b+3b-5=5 | | 4x-12x^2=256 | | 2.7x+45.8=13.2-13.6x | | sin(4x)=-cos(2x) | | y=0.90x+116 | | .05x+.09(3x+20000)=49480 | | .4xy-2=6 | | 7+17t-16t^2=0 | | 2=-4(-2)+2 | | 6x-3y=-2 | | 2x=-4(-2)+2 | | y-(-9)=8/9(x-3) | | 7x^2+37x-30= | | 4-2(7p+4)=-88 | | 2x=-4(0)+2 | | y=80+6*2000 | | 7x^2-19x=-2x^2-5x-5 | | y=80+6*1000 | | 2x=-4(2)+2 | | 2000=80+6x | | 6*-4x=30 | | 6000=80+6x | | 1000=80+6x | | =80+6x | | .3(15d+3c)-.5(8c-10d)= | | -5-12+z=3+4z-3+2z | | 8/5(-0.6)(5/8) | | =2-4x+4*2+5*3 | | =2-3*9.333+4*2+5*3 | | 4b+3=8b-1+5b | | -6+2m(m+2)=5(5-5m) |